Student’s Community Service Involvement: Implications for a Sustainable Community Extension Service - John Mark R. Asio; Dante P. Sardina; Judy Ann O. Olaguir (Asian Journal of Community Services, 2023)
This study aims to determine the student’s community service involvement at a local higher education institution in Olongapo City, Philippines. We used a descriptive-correlation design to 101 students who responded to the online survey during the second semester of the academic year 2021-2022. The result shows that students "highly consider" most of the reasons mentioned in participating to community services. In addition, the top three interests for students in joining community services were education, safety and security, and conservation. As for the skills, the top three include teaching, typing, and cooking. There was no significant difference in the student's involvement when grouped according to gender. However, there was a significant association between the reasons for involvement, interest, and skills beneficial to the student's community service. We shared some implications intended to sustain of community service involvement among students.